Selection of aptamers against the Jagged-1 protein - Fábio Fernando Alves da Silva; Emerson Soares Bernardes (Brazilian Journal of Radiation Sciences, 2022)
The breast cancer is one of the biggest public health problems in the world, being the main female type of cancer that affects the population. The Jagged-1 protein plays an important role in the biology and development of cancer, influencing angiogenesis, growth of neoplastic cells, tumor stem cells, epithelial mesenchymal transition, metastatic processes and resistance to therapies in various types of cancer. In this project, our aim was to select an aptamer for JAG1 ligand using an aptamer library, that could be used as a radiopharmaceutical for PET / SPECT / CT diagnosis of tumors that express JAG1.  Our work showed that MDA-MB-231-JAG1 cells overexpress more mRNA and JAG1 protein than control cells (MDA-MB-231-Control). We also selected aptamers with high affinity for MDA-MB-231-JAG1 cells that could be a useful tool for the development of new radiopharmaceuticals for the diagnosis and treatment of tumors that overexpress JAG1.